2022
DOI: 10.3899/jrheum.220353
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept Withdrawal and Retreatment in Nonradiographic Axial Spondyloarthritis: Results of RE-EMBARK, an Open-Label Phase IV Trial

Abstract: ObjectiveRE-EMBARK investigated etanercept (ETN) withdrawal and re-treatment in patients with non-radiographic axial spondyloarthritis (nr-axSpA) achieving inactive disease (ClinicalTrials.gov:NCT02509026).MethodsPatients received ETN and background NSAID for 24 weeks in Period 1 (P1); those achieving inactive disease (Ankylosing Spondylitis Disease Activity Score with C-reactive protein [ASDAS-CRP] <1.3) discontinued ETN for ≤ 40 weeks (P2). Patients who flared (ASDAS with erythrocyte sedimentation rate [A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Sacroiliitis has been reported to be characterized by an increase in serum levels of various inflammatory markers. For instance, the authors found increased high sensitivity CRP levels in patients with sacroiliitis confirmed by MRI compared to the controls [ 12 ]. Moreover, Jee et al concluded that ESR and CRP were among the inflammatory markers associated with sacroiliitis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sacroiliitis has been reported to be characterized by an increase in serum levels of various inflammatory markers. For instance, the authors found increased high sensitivity CRP levels in patients with sacroiliitis confirmed by MRI compared to the controls [ 12 ]. Moreover, Jee et al concluded that ESR and CRP were among the inflammatory markers associated with sacroiliitis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%